Structural and Functional Brain Patterns of Non-Motor Syndromes in Parkinson’s Disease - Prell, Tino (Frontiers in Neurology, 2018)
Parkinson's disease is a common, progressive and multisystem neurodegenerative disorder characterized by motor and non-motor symptoms. Advanced magnetic resonance imaging, positron emission tomography, and functional magnetic resonance imaging can render the view toward understanding the neural basis of these non-motor syndromes, as they help to understand the underlying pathophysiological abnormalities. This review provides an up-to-date description of structural and functional brain alterations in patients with Parkinson's disease with cognitive deficits, visual hallucinations, fatigue, impulsive behavior disorders, sleep disorders and pain.